Erratum to: Measurement of [ypsilon] production in pp collisions at √s=13 TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; et al. (Journal of high energy physics, 2019)
The top plot shown in figure 3 of ref. [1] is the result of 8 TeV.
Im Text wird Ypsilon als griechischer Buchstabe dargestellt
LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Schmelling, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 758 weitere]
Gesehen am 28.05.2020